A general survey on the customer satisfaction rating of shoppers in the design layout of two bookstores in Metro Manila - Sastre, Evangeline Edio; Faustino, Johanna Acab. (2006.)
This study presented and evaluated the design layout of two bookstores through a random convenience survey among 100 bookstore customers, to determine their level of shopping experience inside the stores. The respondents were asked to answer a thirty-item questionnaire in order to identify their book-shopping lifestyle and how they rate the design of the stores named in the survey. The study also took into account the respondents' opinion and preferences in bookstore design. After analyzing the results, it was concluded that whether customers go into bookstores with the purpose of buying or just browsing, customers seek to derive pleasure from the activity. One way of enhancing the positive shopping experience of customers is by making the store space as functional and appealing as possible. However, the design of the store is largely influenced by many factors such as the store's philosophy, its target customers, and the type and quantity of the merchandise sold. Based on the results and observations, the shoppers tend to lean towards a more relaxed approach to book-shopping, favoring a personal interaction towards the space and the merchandise. Although both bookstores cater to a wide range of customers as their target market, there are differences in selling strategies that each focuses on. As a specialty shop, Bookstore B is more customer service-oriented with a relaxed atmosphere. On the other hand, Bookstore A employs a functional and no-frills approach to its store design to accommodate as much merchandise and people at one time. Even though both stores are run by the same company, the reason why they are designed differently is to offer the public a choice on which merchandise they need or ambiance they are most comfortable with. The study concluded that when bookstores combine organization and excellent service, the stores create a compelling store design that draw customers into the store, keep the customers in and by appropriately showcasing the merchandise, entice people to enjoy themselves and buy.
Thesis (BID)--University of the Philippines Diliman.
Keywords: Bookstores -- Decoration -- Philippines; Consumer satisfaction